Rediscovery of Lustrina Kurian (Hymenoptera, Chrysididae), with redescription of L. assamensis Kurian - Rosa, Paolo; Thai, Pham Hong; Mita, Toshiharu (Zootaxa, 2020)
The genus Lustrina Kurian, 1955 is discussed and Lustrina assamensis Kurian, 1955 is redescribed based on the examination of type specimen as well as a specimen recently collected.